HDR brachytherapy of rectal cancer using a novel grooved‐shielding applicator design. Issue 9 (5th August 2013) - Webster, Matthew J.; Devic, Slobodan; Vuong, Te; Han, Dae Yup; Scanderbeg, Dan; Choi, Dongju; Song, Bongyong; Song, William Y.
Abstract : Purpose: : The aim of this work was to design a novel high‐dose rate (HDR) ( 192 Ir) brachytherapy applicator for treatment of rectal carcinomas that uses tungsten shielding for possibly improved dosimetric results over commercial brachytherapy applicator(s). Methods: : A set of 15 single‐depth applicators and one dual‐depth applicator were designed and simulated using Monte Carlo (MCNPX). All applicators simulated were high‐density tungsten alloy cylinders, 16‐mm in diameter, and 60‐mm long, with longitudinal grooves within which an 192 Ir source can be placed. The single‐depth designs varied regarding the number and depth of these grooves, ranging from 8 to 16 and 1‐mm to 3‐mm, respectively. The dual‐depth design had ten channels, each of which had two depths at which the source could be placed. Optimized treatment plans were generated for each design on data from 13 treated patients (36 fractions) with asymmetrical clinical target volumes (CTVs). All results were compared against the clinically treated plans which used intracavitary mold applicator (ICMA), as well as a recently designed, highly automated, and collimated intensity modulation device named dynamic modulated brachytherapy (DMBT) device. Results: : All applicator designs outperformed the ICMA in every calculated dosimetric criteria, except the total dwell times (∼30% increase). There were clear, but relative, tradeoffs regarding both the number of channels and the depth of each channel. Overall, the 12‐channel, 1‐mm depth, and 14‐channel 2‐mm depth designs had the best results of the simpler designs, sparing the healthy rectal tissues the most while achieving comparable CTV coverage with the dose heterogeneity index and lateral spill doses improving by over 10% and the contralateral healthy rectum dose dropping over 30% compared to ICMA. The ten‐channel dual‐depth design outperformed each single‐depth design, yielding the best coverage and sparing. Conclusions: : New grooved tungsten HDR‐brachytherapy devices have been designed and simulated. The results of this work attest to the capability of these new, highly anisotropic, intelligently shielded applicators to limit dose to healthy tissues while maintaining a conformal prescription dose to the CTV.